Gaudi of Barcelona - Permanyer, Lluis (Rizzoli Interantional Publications, Inc., 1996)
"Gaudí of Barcelona presents the architect's work in Barcelona as it has never been seen before. Vibrant, specially commissioned photographs present the wonders of the Sagrada Família, Casa Milà, and 10 other fantastic creations in Gaudí's home city in unprecedented detail."--Provided by publisher.